Training the Next Generation of Academic Global Neurosurgeons: Experience of the Association of Future African Neurosurgeons - Kanmounye, Ulrick Sidney; Zolo, Yvan; Nguembu, Stéphane; Tétinou, Francklin; Sebopelo, Lorraine Arabang; Endalle, Geneviève; Sichimba, Dawin; Takoukam, Régis; Ghomsi, Nathalie; Jumbam, Desmond T. (Frontiers in Surgery, 2021)
Introduction Although the past decade has seen a substantial increase in African neurosurgeons' academic productivity, productivity remains low compared to their colleagues from other regions. Aspiring neurosurgeons can contribute to the academic neurosurgery workforce by taking care of less technical and time-consuming research tasks. Fortunately, global neurosurgery institutions have also made efforts to increase research exposure and scholarly output in academic global neurosurgery. The Association of Future African Neurosurgeons (AFAN) created a research incubator for aspiring academic global neurosurgeons in Africa to provide enrollees with mentorship, skills, and experience. This study assesses and reports the activities and results of the research incubator. Methods Aspiring academic global neurosurgeons were enrolled in the AFAN Research Incubator Program (ARIP), whose primary objective was to provide enrollees with foundational skills in all aspects of the research cycle. This was organized and led by the first author, an experienced global neurosurgery researcher. Practical activities supplemented the theoretical component of ARIP. Results Fifteen AFAN members aged 25.0 ± 3.0 years enrolled in ARIP: 7 (46.7%) medical students, 4 (26.7%) general practitioners, and 4 (26.7%) residents. Eleven (73.3%) were male, 6 (40.0%) were from Cameroon and 6 (40.0%) had no previous research experience. Two (13.3%) enrollees dropped out. ARIP enrollees published a total of 28 articles, and enrollees published a median of 1.0 (IQR=2) first-author articles on neurosurgical system strengthening. Additionally, ARIP enrollees presented 20 abstracts with a median of one abstract (IQR=3.0). Conclusion South-South research collaborations like ARIP can contribute to improving global neurosurgery research capacity and output. These collaborations can set up the foundations for robust research in low- and middle-income countries.